Effect of coronary disease characteristics on prognostic relevance of residual ischemia after stent implantation. (14th October 2021) - Yang, Y S; Zhang, J Z; Hwang, D H; Lee, J M L; Nam, C W N; Shin, E S S; Doh, J H D; Chen, S L C; Kakuta, T K; Koo, B K K
Abstract: Background: Although residual ischemia after revascularization is an important predictor of future cardiovascular events, its sensitivity and specificity to predict clinical events were relatively low, and data on which coronary disease characteristics affect prognostic implications of residual ischemia are limited. Purpose: We aimed to investigate the influence of coronary disease characteristics on prognostic implications of residual ischemia after percutaneous coronary intervention (PCI). Methods: This study included 1, 476 patients with drug-eluting stent implantation and available pre- and post-PCI fractional flow reserve (FFR) measurements from the international post-PCI FFR registry (NCT04012281). Residual ischemia was defined as post-PCI FFR ≤0.80. Coronary disease characteristics with significant interaction hazard ratios (HRs) for clinical outcomes with residual ischemia were defined as interaction characteristics with residual ischemia (ICwRI). The primary outcome was target vessel failure (TVF)–a composite of cardiac death, target vessel myocardial infarction, and target vessel revascularization–at 2 years. Results: The mean pre- and post-PCI FFR were 0.68±0.11 and 0.87±0.07, respectively. The 203 vessels (13.8%) with residual ischemia had higher risks of TVF compared to that for post-PCI FFR >0.80 (HR 2.45, 95% confidence interval [CI] 1.50–4.00, P<0.001). Among pre- and post-PCI angiographic characteristics, ICwRI with a significant interaction HR with residual ischemia (P<0.10) included lesion length ≥40 mm, pre-PCI SYNTAX score >17, and pre-PCI FFR ≤0.62 (Table). Each ICwRI had a direct prognostic effect not mediated by residual ischemia in mediation analysis. The association between an increased TVF risk and residual ischemia differed according to the number of ICwRI (p-for-interaction <0.001). It was significant in patients with 0 or 1 ICwRI (HR 3.48, 95% CI 2.01–6.00, P<0.001) but not in those with ≥2 ICwRI (HR 0.60, 95% CI 0.18–2.03, P=0.41) (Figure A). Compared to the residual ischemia group, patients without residual ischemia and those with 0 or 1 ICwRI showed a significantly lower risk of TVF (HR 0.32, 95% CI 0.19–0.54, P<0.001), but those with ≥2 ICwRI had a similar risk of TVF as the residual ischemia group (HR 1.08, 95% CI 0.57–2.01, P=0.819) (Figure B). The prognostic impact of ≥2 ICwRI in patients without residual ischemia was consistent in all subgroups with different clinical characteristics. Conclusions: Coronary disease characteristics including lesion length, SYNTAX score, and pre-PCI FFR affected the prognostic implications of residual ischemia. This prognostic relevance was attenuated in patients with multiple interacting characteristics. Therefore, comprehensive assessment of coronary disease characteristics with post-procedural coronary physiology can help better risk stratification and appropriate treatment planning after revascularization. Funding Acknowledgement: Type of funding sources: None.